PENGARUH JARAK DAN POLA PREFABRICATED VERTICAL DRAIN (PVD) PADA PERBAIKAN TANAH LEMPUNG LUNAK = EFFECT OF DISTANCE AND PATTERN OF PREFABRICATED VERTICAL DRAIN FOR IMPROVEMENT OF SOFT CLAY SOIL - Wimpie Agoeng Noegroho Aspara; Eka Nur Fitriani (Majalah Ilmiah Pengkajian Industri, 2016)
AbstractIf a structure for reasons of technical, economic, social, or startegic is to be built on a soft ground, then there are usually two problems to be solved, namely the low geotechnical bearing capacity and large soil deformation with sometimes differential settlement. Pre-compression is a foundation soil compression process with the provision of temporary loading (preloading) before actually constructing a building. Pre-fabricated vertical drain is a synthetic drainage system installed vertically inside soft soil layers. Soil condition at the project activity is a relatively very soft clay soil with relatively high coefficient of consolidation resulting in very long period of consolidation process. Therefore, it is needed advance soil improvement by prealoding of pre-fabricated vertical drain. Spacings of installed PVD vary, those are 50 cm, 100 cm, 150 cm, and 200 cm with a pattern of triangles and rectangles. Based on the analytical calculation, it is resulted that optimum PVD distance to achieve 90% consolidation is 150 cm with a triangular pattern. The time of consolidation was achieved within four months. AbstrakKetika suatu struktur karena alasan-alasan teknis, ekonomi, sosial, atau strategis terpaksa didirikan di atas tanah lunak, maka biasanya ada dua masalah geoteknik yang harus dipecahkan yaitu daya dukung yang rendah dan penurunan serta beda penurunan yang besar. Prakompresi adalah suatu proses pemampatan tanah pondasi dengan jalan pemberian pembebanan sementara (prabeban/preloading) sebelum konstruksi yang sesungguhnya didirikan. Prefabricated vertical drain (PVD) adalah sistem drainase buatan yang dipasang vertikal di dalam lapisan tanah lunak. Kondisi tanah di lokasi kegiatan relatif sangat lunak dengan koefisien konsolidasi relatif sangat tinggi mengakibatkan proses konsolidasi berjalan relatif sangat lama. Untuk itu diperlukan perbaikan tanah terlebih dahulu dengan prealoading menggunakan PVD. Jarak spasi antar PVD yang dipasang bervaiasi yaitu 50 cm, 100 cm, 150 cm, dan 200 cm dengan pola konfigurasi segitiga dan segiempat. Berdasarkan hasil perhitungan secara analitis didapatkan jarak optimum PVD untuk mencapai konsolidasi 90% adalah 150 cm dengan pola segitiga dengan proses konsolidasi dicapai selama waktu penurunan 4 bulan.